Cyrhetrenyl and Cymantrenyl N-Acylhydrazone Complexes Based on Isoniazid: Synthesis, Characterization, X-Ray Crystal Structures and Antitubercular Activity Evaluation - Lemus-Chavez, L; Lemus-Chavez, L (Elsevier B.V., 2022)
Four organometallic N-acylhydrazones of the general formulae [M{(η5-C5H4)-CH[dbnd]N[sbnd]NH[sbnd]C(O)-(C5H4[sbnd]N)}(CO)3] [(with M = Re (5a) or Mn (6a)] and [M{(η5-C5H4)-C(Me)=N[sbnd]NH[sbnd]C(O)-(C5H4[sbnd]N)}(CO)3] [(with M = Re (5b) or Mn (6b)] were prepared by reaction of aldehyde/methyl ketone organometallic precursors with isoniazid (INH). All compounds were fully characterized using conventional spectroscopic techniques (FT-IR, 1H and 13C{1H} NMR, mass spectrometry, and high-resolution mass spectrometry). The X-ray crystal structures of cyrhetrenyl compounds (5a and 5b) are also reported. This structural analysis indicated that both compounds exhibited an E-configuration of the substituents on the -C(R1)=N- (R1 = H or Me). The biological activity of the four analogous organometallic compounds (5 and 6) to INH and their organics counterpart {[(C6H5)-C(R)=N[sbnd]NH[sbnd]C(O)-(C5H4[sbnd]N)] where R = H (NAH[sbnd]H) or R = Me (NAH-Me)} were evaluated on Mycobacterium tuberculosis (M. tuberculosis) in the standard strain H37Rv ATCC 27,294. The replacement of a hydrogen atom by a methyl group on the acylhydrazone moiety led to a significant increase in antitubercular properties. The compounds 5b and 6b (R1 = Me) were at least 36- and 18-fold more effective than 5a and 6a (R1 = H), respectively. The cyrhetrenyl derivative (5b) was the most active complex against M. tuberculosis. This compound was shown to be about 2-times more effective than its organic analog (NAH-Me) and showed activity comparable to antitubercular drug INH. In vitro toxicity assays against murine macrophage cells J774A.1 (ATCC TIB-67) were also conducted, and selectivity indexes were determined for the most promising compounds. All N-acylhydrazones showed a moderated cytotoxic profile, similar to the isoniazid and rifampicin (RIF) control drugs, while 5b exhibited better selectivity index (SI) concerning the organic counterpart NAH-Me. Based on the anti-TB activity, cytotoxicity, and selectivity index, compound 5b has more potential for evolution as a new antitubercular agent. © 2022